Diversity of Earthworms (Oligochaeta: Annelida) in Reclamation Land at PT. Bukit Asam (Persero) Tbk. Tanjung Enim, South Sumatera - Rita Oktavia (Budapest International Research and Critics University, 2019)
The earthworms are in the restoration program first needs to know diversity and species that have the potential to restore ecosystem function. In this study, the aim is the researcher examined the diversity of earthworms in post-mining land at various ages of revegetated land, non-revegetated land, and natural land. The research was conducted at PT. Bukit Asam (Persero) Tbk, Tanjung Enim, South Sumatra. The methodology is used the quantitative research to find the result of this research. The result is The total number of individuals earthworms, and the highest density was found on 23-year-old revegetated land and natural land.